2016
DOI: 10.1007/s11626-016-0045-x
|View full text |Cite|
|
Sign up to set email alerts
|

Down-regulation of miR-181a can reduce heat stress damage in PBMCs of Holstein cows

Abstract: Heat stress can weaken the immune system and even increase livestock's susceptibility to disease. MicroRNA (miR) is short non-coding RNA that functions in post-transcriptional regulation of gene expression and some phenotypes. Our recent study found that miR-181a is highly expressed in the serum of heat-stressed Holstein cows, but the potential function of miR-181a is still not clarified. In this study, peripheral blood mononuclear cells (PBMCs), isolated from Holstein cows' peripheral blood, were used to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…Furthermore, the inhibition of miRNA counteracted the negative effects of the overloading HP on these factors and enhanced those of a low cyclic pressure. Additionally, it has been reported that the transient transfection of miR-34a, miR-146a, and miR-181a down-regulated the expression of antioxidant enzymes with a simultaneous decrease of mitochondrial intracellular ROS levels in PBMC of Holstein cows, in HUVEC lines, and in primary OA chondrocytes and synoviocytes [29,30,56,57]. According to this evidence, in this study, the silencing of miR-34a and miR-181a reduced the production of mitochondrial superoxide anion and the mRNA levels of SOD-2 and NRF2 in OA chondrocytes, increasing the activity of low cyclic HP and limiting the effects of static continuous loading.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the inhibition of miRNA counteracted the negative effects of the overloading HP on these factors and enhanced those of a low cyclic pressure. Additionally, it has been reported that the transient transfection of miR-34a, miR-146a, and miR-181a down-regulated the expression of antioxidant enzymes with a simultaneous decrease of mitochondrial intracellular ROS levels in PBMC of Holstein cows, in HUVEC lines, and in primary OA chondrocytes and synoviocytes [29,30,56,57]. According to this evidence, in this study, the silencing of miR-34a and miR-181a reduced the production of mitochondrial superoxide anion and the mRNA levels of SOD-2 and NRF2 in OA chondrocytes, increasing the activity of low cyclic HP and limiting the effects of static continuous loading.…”
Section: Discussionmentioning
confidence: 99%
“…The bta-miR-181a is known to be involved in various cellular biological processes including cell proliferation and apoptosis 57 . The impact of bta-miR-181a in peripheral blood mononuclear cells (PBMC) subjected to HS showed that inhibiting the miRNA would reverse the HS damage and improve the viability of PBMCs in Holstein cows 58 . The involvement of miRNAs in stress response is well known and EV-coupled miRNAs are differentially expressed in response to metabolic stress 30 .…”
Section: Discussionmentioning
confidence: 99%
“…The gene expression of miR-34a and miR-181a is induced by the oxidative stress stimulus as demonstrated in different studies from human cardiac and carcinoma cell lines and in OA chondrocytes [4,46,47]. Moreover, the inhibition of miR-34a and of miR-181a decreased the expression of antioxidant enzymes with a concomitant reduction of mitochondrial intracellular ROS levels in primary mesangial cells, in PBMC of Holstein cows and in HUVEC lines [48,49]. According to the current literature, transfection of our OA cells with miR-34a and miR-181a specific inhibitors significantly down-regulated the expression of antioxidant enzymes as well as the production of mitochondrial superoxide anion, particularly preventing their induction by visfatin.…”
Section: Discussionmentioning
confidence: 99%